Development of Interactive Multimedia Computer-Assisted Learning Method for Empowering Breastfeeding Mothers in Family Learning Centers - Susilawati, Dewi; Nilakesuma, Nur Fajdri; Musharyadi, Feri (Poltekkes Kemenkes Jakarta III, 2025)
The low achievement of exclusive breastfeeding is a public health problem worldwide. Exclusive breastfeeding coverage in Indonesia in 2023 was recorded at only 67.94%, down from 2022. One contributing factor is the lack of support for breastfeeding mothers. Various strategies can be implemented to enhance family involvement, one of which is education through a family center learning approach. One method that can be used in providing education is the computer assisted learning (CAL) method. Develop interactive multimedia with the CAL method that can be used in family center learning to empower breastfeeding mothers. ADDIE model, to produce CAL-based multimedia applications. The method used to collect data was questionnaires and data analysis using descriptive statistics. Computer Assisted Learning-based multimedia design named